INTERAKSI SOSIAL WARGA BELAJAR INKLUSI DENGAN WARGA BELAJAR NORMAL DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) BINA KREASI KOTA PEKANBARU - Van FC, Syukri Themistu; Achmad, Said Suhil; Sumardi, Sumardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The wording in this study is how is the social situation of the Community Learning Center (PKBM) institution in Pekanbaru City Bina Kreasi? What is the pattern of social interaction between autistic learners and normal learners in the Community Learning Activity Center (PKBM) in Pekanbaru City? The benefits of this study were finding out the social situation of the PKBM Creation institution and the patterns of social interaction of the autistic learning community with normal pupils in the Community Learning Activity Center (PKBM) in Pekanbaru City Bina Kreasi. This research is descriptive with a qualitative approach. Data collection techniques used by observation and interviews. The subjects of this study were 4 people consisting of 1 autistic child and 3 tutors at PKBM Bina Kreasi as informers. The data validity technique used in this study is tringulation. The data analysis technique used is through data reduction, data presentation and conclusionsKey Words: Social interaction, learning from citizens, in PKBM Creative Development